Analisis Pengaruh Pengawasan dan Kemampuan Kerja Terhadap Kinerja Karyawan Melalui Kualitas Pelayanan Publik di Kantor Bank Jatim Cabang Sumenep - Fara Aryanti Risma Ayu; Hadi Susanto; Sri Mulyani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Fara Ariyanti Risma Ayu, 2025. Analysis of the Influence of Supervision and Work Ability on Employee Performance through Public Service Quality at Bank Jatim Sumenep Branch Office. Postgraduate Program, Wijaya Putra University, Surabaya. This study uses a quantitative approach with an explanatory research type and involves 86 respondents. Data analysis was conducted using Smart PLS. The purpose of the study was to determine the direct and indirect effects of supervision and work ability on employee performance, with public service quality as a mediating variable. The results of the study indicate that: (1) Supervision has a significant effect on public service quality, but is not significant on performance directly; (2) Work ability has a significant effect on service quality and employee performance; (3) Public service quality has a significant effect on employee performance; (4) Supervision and work ability also have an indirect effect on performance through public service quality.